Analisis Kebutuhan Pengembangan Bahan Ajar Berupa Modul Elektronik Berbasis STEM - Rasmi, Dian Pertiwi; Hendri, Menza; Azriyanti, Riza (Postgraduate, University of Mataram, 2023)
The purpose of this study was to analyze the needs of teachers for the development of teaching materials in the form of STEM-based electronic modules. Development using the ADDIE model (Analysis, Design, Development, Implementatin, Evaluation). The data obtained through interviews with one of the physics teachers in Kerinci district, the results of the interviews are that in the learning process teachers have not used electronic modules with the STEM approach and require electronic modules with the STEM approach because the STEM approach focuses more on real-world problems or problems in everyday life. based on a combination of four aspects, namelyÂ Science, Technology, Engineering, and Mathematics, making it easier for students to understand the material, besides that it can also improve students' scientific literacy. So that researchers will carry out the development of STEM-based electronic modules.